Meditation and sleep quality: integrative review (Research, Society and Development, 2023)
To review the available scientific content regarding the relationship between meditation and sleep quality PubMed, Scopus and Web of Science databases were searched with the keywords “meditation”, “sleep” and “sleep disorder”. Articles were considered if published in English or Portuguese, between 2011 and 2022 attended to the following criteria: (1) reported data from an original study, (2) presented objective documentation of meditation’s outcomes, and (3) performed in adults. Articles that did not meet the inclusion criteria and presented pharmaceutical intervention were excluded. Overall, the studies in this review had a positive outcome on sleep quality after meditation. In some articles, a couple of diseases were presented with less severity on the ongoing condition after the practices. In addition, they helped with attention, perception, analytical ability, motor response and reaction time of people that performed it. Moreover, it brought effective results for the treatment of chronic insomnia, resulting in significant improvements in total sleep time, in the Pittsburgh Sleep Quality Index and improved sleep quality in individuals with chronic insomnia. Of the 14 studies included in this review, 9 were randomized controlled trials and 5 were population-based surveys. The outcomes of mindfulness meditation practice were diverse, ranging from improved sleep and life quality, reduction of sleep-related problems, positive interference with psychological problems, memory, and concentration. Despite positive results, there must be a methodological standard among the studies regarding this subject, with the aim to find reliable results that can be used for substantial clinical interventions.